2021
DOI: 10.1038/s41598-021-89329-7
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory responses to metal oxide ceramic nanopowders

Abstract: Ceramic orthopaedic implants are increasingly popular due to the need for robust total joint replacement implants that have a high success rate long-term and do not induce biological responses in patients. This study was designed to investigate the biological effects of ceramic nanopowders containing aluminium oxide or zirconium oxide to activate the human macrophage THP-1 cell line. In vitro investigation of pro-inflammatory gene expression and chemokine secretion was performed studied using RT-qPCR and ELISA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 45 publications
2
12
1
Order By: Relevance
“…In physiological environment, alumina is an inert material matrix, which is non-absorbable and extremely hard. Al 2 O 3 appeared to have no significant cytotoxic effect ( Jamieson et al, 2021 ), however, aluminium is not considered to exhibit osteogenic properties and even recognized for having adverse effects on osteoblasts ( Yang et al, 2018 ). To overcome these limitations, some composites have been developed from two or more materials to obtain the excellent properties of a single material.…”
Section: Specific Types Of Barrier Membranesmentioning
confidence: 99%
“…In physiological environment, alumina is an inert material matrix, which is non-absorbable and extremely hard. Al 2 O 3 appeared to have no significant cytotoxic effect ( Jamieson et al, 2021 ), however, aluminium is not considered to exhibit osteogenic properties and even recognized for having adverse effects on osteoblasts ( Yang et al, 2018 ). To overcome these limitations, some composites have been developed from two or more materials to obtain the excellent properties of a single material.…”
Section: Specific Types Of Barrier Membranesmentioning
confidence: 99%
“…Also, the type of biomaterial implanted can impact the maturation of dendritic cells which activate the adaptive immune system (Carroll et al, 2016). Metal debris from COI has previously been linked to the development of inflammatory pseudotumours (Jamieson et al, 2021). Pseudotumours are made of soft tissue mass composed of different inflammatory cells such as macrophages and T cells which are localized near the COI (Hart et al, 2012).…”
Section: Implant Debris Associated Inflammation Oxidative Stress and ...mentioning
confidence: 99%
“…Given the above-mentioned implant-associated inflammatory processes, different prosthetic materials have been tested for toxicity and immunogenicity in numerous in vitro studies by measuring viability and activation of immune cells (peripheral blood mononuclear cells (PBMCs), macrophages, macrophagic cell lines) and pre-osteoblast cells [ 4 , 21 , 22 ]. Macrophages and osteoblasts can phagocyte alumina (Al 2 O 3 ) nanoparticles, which causes activation of an inflammatory response and cytokine release [ 23 , 24 ]. Several studies have shown that Al 2 O 3 particles can activate the immune response; however, there is controversy in the reports about their toxicity and the effect on human cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…Radziun et al reported that Al 2 O 3 nanoparticles are capable of penetrating the membranes of the L929 mouse fibroblast cell line and the BJ human fibroblast cell line without a significant decrease in cellular viability [ 26 ]. A recent report, however, in which THP-1 macrophages were treated with Al 2 O 3 demonstrated that Al 2 O 3 nanoparticles induced the inflammasome in THP-1 macrophages via activation of the Toll-like receptor 4 (TLR4) pathway [ 23 ]. In that study, 24 h treatment with Al 2 O 3 or zirconia (ZrO 2 ) at the concentration of 50 µm 3 /cell caused upregulation of interleukin 8 ( IL-8 ), CC-chemokine ligand 2 ( CCL2 ), CCL3, and CCL4 expression while not affecting cell viability [ 23 ].…”
Section: Introductionmentioning
confidence: 99%